An IEC 61131-3 compiler for the MatPLC - Mário Jorge Rodrigues de Sousa (2003)
We have implemented an IEC 61131-3 IL (Instruction List) and ST (Structured Text) compiler that will be part of an open source PLC. In doing so, several issues were found regarding the specification of the IL and ST languages, produced by the IEC (International Electrotechnical Commission) standards body. The uncovered issues are discussed in this paper, and some changes to the standard are proposed. The architecture used in the compiler implementation is also outlined in the paper.